APLIKASI SISTEM PEMANTAUAN PEMAKAIAN KARTU KREDIT BERBASIS WEBSITE PADA PT GMF AEROASIA Tbk UNIT MARKETING & BUSINESS DEVELOPMENT - Nur Azizah; Handy Januar Permana; Budi Heryatna (LPPM Unbaja, 2019)
The faster the development of information technology in the world both in operational activities and nonoperationalactivities, one of which is the report on the use of corporate credit cards which must be accurate,accurate and relevant. In preparing the income report a computerized system is needed, so that every runningprocess in making credit card usage reports can run effectively and efficiently and be balanced with adequatehuman resources. But in its implementation, at PT. GMF Aeroasia Marketing & Business Development unit,does not have a system that covers all activities, one of which is on G.M. and AMS in making credit card usagereports still using Ms. Excel so that the media used is still very likely to cause human error so that a credit cardusage monitoring system is needed to produce the report. This study uses the PIECES analysis method(Performance, Information / Data, Economy, Control, Efficiency, Service), system requirements elicitation, andsystem modeling using UML (Unified Modeling Language) to visualize, which is then implemented with theHypertext Preprocessor programming language (PHP) with the MySQL-Server database as the database used.With the existence of a credit card usage monitoring system, it can make it easier for G.M and AMS to produceaccurate credit card usage reports at a fast time, so that they can create effective and efficient performance, andcan support evaluation in the internal control of the report manager.